Nomogram-based prediction of the risk of AVF maturation: a retrospective study - Zhao, Bin; Wang, Hui; Wang, Yuzhu; Zhan, Shen; Yu, Pei (Frontiers in Medicine, 2024)
Autogenous arteriovenous fistulas are recommended by international guidelines as the the preferred vascular access for hemodialysis patients .To increase the rate of arteriovenous fistula (AVF) use ,early identification of autogenous arteriovenous fistula (AVF) maturation failure and timely implementing effective interventions to prompt AVF maturity are very important. In this work, we retrospective selected 702 patients with newly created AVF and divided into mature and non-mature groups according to whether arrived clinical or ultrasound criteria at one,three months.Finally, we used the nomogram to establish a predictive model of maturation through compared clinical features and ultrasound measurements between two groups ;Based on these results, this model will help clinicians to decide whether and when to perform an assisted maturation intervention. We believe that two aspects of this manuscript will make it interesting to general readers of your journal.